2002
DOI: 10.1046/j.1365-2249.2002.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical efficacy and safety of pascolizumab (SB 240683): a humanized anti-interleukin-4 antibody with therapeutic potential in asthma

Abstract: SUMMARYThe type 2 helper T cell (T H 2) cytokine interleukin (IL)-4 is thought to play a central role in the early stages of asthma. In an effort to develop an antibody treatment for asthma that neutralizes the effects of IL-4, a murine monoclonal antibody, 3B9, was generated with specificity for human IL-4. In vitro studies demonstrated that 3B9 inhibited IL-4-dependent events including IL-5 synthesis, T H 2 cell activation and up-regulation of immunoglobulin E expression. 3B9 was then humanized (pascolizumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(93 citation statements)
references
References 22 publications
1
88
0
3
Order By: Relevance
“…PV'de yeni sitokin paternlerinin tanımlanmasının potansiyel terapotik seçimlere ışık tutacağı düşünülmektedir 6 . Yapılan çalışmalara bakıldığında Th2 lenfosit alt grubunun hakim olduğu IL-4 yüksekliğiyle seyreden astım gibi alerjik kökenli hastalıklarda monoklonal anti IL-4 antikor tedavisi ve IL-4 reseptör tedavisi ile başarılı sonuçlar elde edildiği gözlenmiştir 37,38 . 11 .…”
Section: Discussionunclassified
“…PV'de yeni sitokin paternlerinin tanımlanmasının potansiyel terapotik seçimlere ışık tutacağı düşünülmektedir 6 . Yapılan çalışmalara bakıldığında Th2 lenfosit alt grubunun hakim olduğu IL-4 yüksekliğiyle seyreden astım gibi alerjik kökenli hastalıklarda monoklonal anti IL-4 antikor tedavisi ve IL-4 reseptör tedavisi ile başarılı sonuçlar elde edildiği gözlenmiştir 37,38 . 11 .…”
Section: Discussionunclassified
“…IL-4 inhibition was evaluated by Hart et al using a pascolizumab which is a humanized anti-IL-4 monoclonal antibody [59]. Although the in vivo studies demonstrated a good tolerability of the drug, trials were aborted because pascolizumab did not significantly reduce circulating IgE [60].…”
Section: Immunotherapymentioning
confidence: 99%
“…Pascolizumab is a humanized anti-IL-4 mAb that inhibits the binding of IL-4 to its receptor [Hart et al 2002]. IL-4 is a cytokine thought to have a role in the early stages of asthma by its involvement in isotype switching to IgE production, eosinophil chemotaxis, Th2 differentiation, and effector T-cell responses [Pauwels et al 1998;Ricci, 1994].…”
Section: Pascolizumabmentioning
confidence: 99%